A Story-Based Virtual Laboratory Practicum in an Undergraduate Genetics Course to Improve Concept Understanding and Visual Literacy - Fibriana, Fidia; Abidin, Zaenal; Naufal, M Ahganiya; Febriyanto, Hendra; Alma’ruf, Fattah; Nurazizah, Kaylha Salsabilla; Ningrum, Nuraini Septia; Upaichit, Apichat (Biosaintifika: Journal of Biology & Biology Education, 2025)
Genetic concepts, particularly DNA technology, often lead to misconceptions among students. Integrating a virtual laboratory (VL) into coursework presents an innovative approach to enhancing concept understanding and visual literacy through interactive, story-based simulations that bridge theory and practice. This study aimed to analyze the students' concept understanding and visual literacy improvement by applying a VL to teach DNA Test Simulation (Paternity Test) using a contextual narrative method. The research was conducted in the Science Education undergraduate program with a purposive total sampling of students enrolled in Genetics (First Semester 2024/2025), utilizing an open-source web-based VL platform. Pretest and posttest assessments measured students' concept understanding and visual literacy before and after VL integration. The findings reveal a significant improvement, with concept understanding rising from an average pretest score of 42.6 to posttest 69.9 (N-Gain 0.46) and visual literacy increasing from 53.8 to 71.8 (N-Gain 0.37). Furthermore, 97% of students were satisfied with the VL-based learning method. This research contributes to knowledge and science development by demonstrating that VL can improve concept learning and visual literacy in genetics education. It offers an accessible and scalable solution for teaching complex DNA technology concepts, reducing reliance on costly wet laboratory experiments while maintaining scientific rigor. Beyond academia, the study supports broader educational equity, making advanced molecular biology concepts more available to diverse learners and fostering scientific literacy in society.